Prediksi Harga Minyak Dunia Dengan Fuzzy Time Series - Ramadhani, Muta’ Alya; Mustawinar, Besse Helmi; Arifanti, Dwi Risky; Yuliani, Yuliani (Universitas Cokroaminoto Palopo, 2024)
The government uses economic growth as a metric to measure prosperity and the effectiveness of economic development. However, oil price fluctuations can increase inflation through increasing fuel prices and have an impact on the world economy, including Indonesia. This research will apply a fuzzy time series using the Cheng method to predict world oil prices. The results of this research show that the MAPE value for forecasting world oil prices using the Fuzzy Time Series Cheng method is 2%, which means the forecasting model has very good value.